3D printing of high-resolution PLA-based structures by hybrid electrohydrodynamic and fused deposition modeling techniques. (11th January 2016) - Zhang, Bin; Seong, Baekhoon; Nguyen, VuDat; Byun, Doyoung
Abstract: Recently, the three-dimensional (3D) printing technique has received much attention for shape forming and manufacturing. The fused deposition modeling (FDM) printer is one of the various 3D printers available and has become widely used due to its simplicity, low-cost, and easy operation. However, the FDM technique has a limitation whereby its patterning resolution is too low at around 200 μ m. In this paper, we first present a hybrid mechanism of electrohydrodynamic jet printing with the FDM technique, which we name E-FDM. We then develop a novel high-resolution 3D printer based on the E-FDM process. To determine the optimal condition for structuring, we also investigated the effect of several printing parameters, such as temperature, applied voltage, working height, printing speed, flow-rate, and acceleration on the patterning results. This method was capable of fabricating both high resolution 2D and 3D structures with the use of polylactic acid (PLA). PLA has been used to fabricate scaffold structures for tissue engineering, which has different hierarchical structure sizes. The fabrication speed was up to 40 mm/s and the pattern resolution could be improved to 10 μ m.